Driving Factors and Actions Taken by Women to Confront Violence: Qualitative Research Based on Art - Arboit, Jaqueline (Journal of interpersonal violence, 2022)
This qualitative study based on art aimed to analyze the critical path of women in coping with situations of violence in the city of Santa Maria/Rio Grande do Sul, Brazil, in these women’s perspective. It has as settings the Women’s Police Station (DEAM) and the institutional care service for women in situations of violence, named Casa Abrigo (Shelter House). The “talking map” creativity and sensitivity technique was used in conjunction with the in-depth interview to analyze the critical path of 12 women in situations of violence. The driving factors of the critical path of women in coping with situations of violence were related to their knowledge about the DEAM’s assistance, their perceptions about the experience of different types of violence, the fact that they can no longer stand the violence and that they worry about their children, as well as the support of their family, of the ex-husband’s or ex-partner’s relatives, and of their female friends. The decisions executed and actions taken by the women included reporting the aggressor, requesting a restraining order, seeking help from the guardianship council and family members, getting back together with the aggressor, and leaving home. There is a need to strengthen the decision-making process of women in situations of violence to break the silence and the situation of violence. For this purpose, it is urgent to broaden the information for and knowledge of women about where and how to seek help, through access to clear and precise information in all places that compose the assistance network for these women.